2012
DOI: 10.3109/10428194.2011.624226
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic evaluation of oxidative stress markers in an immunohistochemical study of B-cell derived lymphomas

Abstract: Although oxidative stress plays an important role in the biology of solid malignant tumors, little is known about oxidative stress in hematological malignancies. In this study, we evaluated the immunohistochemical expression and clinical correlations of oxidative stress markers and several essential antioxidant enzymes in B-cell lymphomas. Paraffin-embedded diagnostic tissue samples from 18 diffuse large B-cell lymphomas (DLBCL), 18 follicular lymphomas (FL), 19 Hodgkin lymphomas (HL), 7 chronic lymphocytic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…We have previously carried out thorough evaluation of the expression of oxidative stress markers in different forms of lymphoma. In a recent study [22] we found that high levels of GCL and nitrotyrosine, and also low levels of MnSOD correlated with poor prognosis, but the number of patients with DLBCL in that study was only 18. The aim of the present study was to assess the relationships between antioxidant enzymes, oxidative stress markers and prognosis in cases of diffuse large B-cell lymphoma treated in the rituximab era.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We have previously carried out thorough evaluation of the expression of oxidative stress markers in different forms of lymphoma. In a recent study [22] we found that high levels of GCL and nitrotyrosine, and also low levels of MnSOD correlated with poor prognosis, but the number of patients with DLBCL in that study was only 18. The aim of the present study was to assess the relationships between antioxidant enzymes, oxidative stress markers and prognosis in cases of diffuse large B-cell lymphoma treated in the rituximab era.…”
Section: Discussionmentioning
confidence: 90%
“…Intensities were discovered to be better suited to assess survival estimates. Staining patterns were discovered and analyzed in our previous study [22]. The staining intensity of cytoplasmic 8-OHdG correlated with high Trx (p = 0.011) and GCL (p = 0.0003) intensities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, radiotherapy and chemotherapeutic agents (such as ABVD) used in the treatment of Hodgkin lymphoma are largely based on ROS generation. There is also emerging evidence for other B‐cell malignancies that the malignant B cells are under metabolic oxidative stress and may have altered antioxidant enzyme expression …”
Section: Introductionmentioning
confidence: 99%
“…Immunostaining was performed as described previously,16 with a few modifications. The glass slides were incubated in 1.5% H 2 O 2 solution instead of 3% H 2 O 2 , and they were washed with Tris-buffered saline instead of phosphate buffered saline between the different steps of staining.…”
Section: Methodsmentioning
confidence: 99%